1990
DOI: 10.1128/jvi.64.2.944-949.1990
|View full text |Cite
|
Sign up to set email alerts
|

Bovine papillomavirus E2 repressor mutant displays a high-copy-number phenotype and enhanced transforming activity

Abstract: The methionine codon at bovine papillomavirus type 1 nucleotide 3091 was mutated to determine whether it may serve as an initiation codon for an E2 transcriptional repressor protein and to determine the role of the repressor in the biological activities of the virus. A series of transient expression experiments with CV1 cells documented that the mutation reduced expression of repressor activity from the viral genome and resulted in increased expression of the E5 transforming gene. Viral genomes containing the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
14
0

Year Published

1990
1990
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 41 publications
3
14
0
Order By: Relevance
“…repress E2 transactivation (data not shown), in agreement with the finding that this ATG codon is utilized for translation initiation of E2-TR (21). The capacity for this mutation to disrupt E2-TR expression is further described in the accompanying paper by Riese et al (35).…”
supporting
confidence: 85%
See 2 more Smart Citations
“…repress E2 transactivation (data not shown), in agreement with the finding that this ATG codon is utilized for translation initiation of E2-TR (21). The capacity for this mutation to disrupt E2-TR expression is further described in the accompanying paper by Riese et al (35).…”
supporting
confidence: 85%
“…This change in relative abundance was significant, despite an increased level of E8/E2 expression by this mutant (Table 1). A similar study was performed on an identical ATG missense mutant at nt 3092 and arrived at a similar conclusion that disruption of E2-TR resulted in an increase in the potential of the virus to transactivate, replicate, and transform (35). It will be of interest to understand the consequences of disrupting E2-TR expression in dermal fibroblasts and in basal epithelial cells of a bovine fibropapilloma.…”
Section: Notes 955mentioning
confidence: 76%
See 1 more Smart Citation
“…Therefore, it seems probable that maintenance of BPV as a multicopy episome over numerous generations requires a finely tuned regulatory system. It has been shown that mutation of one form of E2 affects the level of the other forms and that E2 repressor mutants display a high-copy-number phenotype (19,20,34). These findings, together with our results that all promoters respond to the E2 activator through the URR and that no other BPV gene products are involved, suggest that viral homeostasis could be maintained by a delicate balance between the E2 activator and repressor proteins.…”
Section: Our Comparison Of the Abundance Of Messages Expressedsupporting
confidence: 70%
“…Since at least the P2 and P4 promoters have been shown to be regulated by the E2 activator and repressor proteins in a URR-dependent manner (8,9,12,33,40,41), it is possible that an autoregulatory circuit based on the E2 proteins is crucial for control of BPV gene expression. Indeed, it appears that a precise regulation of gene expression is necessary for control of BPV copy number, since mutations in the E2C repressor result in a high-copy-number phenotype in stably transformed cell lines (20,34). In addition, repressor mutants replicate to higher levels than the wild type in transient replication assays (47).…”
mentioning
confidence: 99%